Shape-Based Matching Vision System in Flexible Manufacturing System - Lim , Wee Teck; Sulaiman , Marizan; Mohd Shah, Hairol Nizam (2010)
This research is regrading the application of a vision algorithms ro monitor the operations of a system in order to control the decision making concerning jobs and work pieces recorgnition that are to be made during system operation in real time.